Managing subjectivity in arts assessment - Baptiste, Lennise (School of Education, UWI, St. Augustine, 2008)
Transparency in the award of scores is a major concern in arts assessments. Subjectivity impacts on assessment of the arts due in the main to disagreements about the artistic skills and aesthetic dimensions of artistic works. This paper describes some of the dilemmas facing judges across the artistic domains, and identifies questions that can guide the assessment of creativity. Rubrics are discussed as a method of reducing the impact of subjectivity in arts assessments
Keywords: Arts education; Student evaluation; Subjectivity; Caribbean